Pengembangan Instrumen Penilaian Kognitif dalam Pembelajaran Tematik Kelas V Sekolah Dasar - Utami, Diah Ayu Putri; Wardani, Naniek Sulistya (STKIP PGRI Bandar Lampung, 2020)
The purpose of this research is to (1)know about how to develop cognitive instrument assessment of thematic grade 5 elementary school;(2)to know about quality of cognitive instrument of thematic grade 5 elementary school from classical item analysis. This RND research consists of preliminary studies, product development and product trials. The subjects of this study were 5th grade students at Dorolegi 1 ES, Ketangirejo 1 ES and Sindurejo 1 ES Grobogan. The results showed that (1)how to develop cognitive assessment instruments namely determining theme, IC, BC, GPA, learning objectives, measuring instruments, grids, items, trials, revisions and determining the final product (2) Instrument items shaped PG consists of 42 items. Based on the classical analysis, items had high validity r≥0.20, reliability α≥0.20 (α = 938), moderate difficulty level 0.25 <P≤0.75, distinguishing power received P≤0.20, deception 59.5% is very good and 40.5% is good. Thus, the cognitive assessment instrument for thematic learning in 5th grade elementary school is feasible to use.